František Weyr – the Most Important Czech Lawyer of the First Half of the 20th Century - Tauchen, Jaromír (Pázmány Law Review, 2025)
This article highlights the outstanding significance of František Weyr (1879–1951) for legal scholarship in Czechoslovakia in the first half of the 20th century. The focus is on his professional career, his scholarly contributions and his intellectual legacy, with particular emphasis on his role in the development of normative legal theory. Weyr is considered one of the founders of the Brno Normative School and made a significant contribution to the development of legal science in the Czech lands. He was a friend and intellectual partner of Hans Kelsen, whose Pure Theory of Law inspired him, although he developed his own conception of legal normativity. The article also deals with his work at Masaryk University and his public engagement.